An evaluation of dextrose, lactose, and whey sources in phase 2 starter diets for weanling pigs - Bergstrom, J.R.; Groesbeck, C.N.; Benz, J.M.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
Two experiments were conducted to evaluate the effects of various dextrose, lactose, and whey sources on weanling pig performance. In Exp. 1, a total of 228 pigs (initially 17.1 lb) were used in a 14-d experiment. There were six treatments consisting of a control (corn-soybean meal diet) or the control diet with 7.2% lactose, 7.2% dextrose anhydrous, 7.2% dextrose monohydrate, 10% feed-grade whey, or 10% food-grade whey. Pigs were blocked by weight and randomly allotted to treatment after being fed SEW and Transition diets for the first seven days post-weaning. Overall, ADG and d 14 weight were improved (P<0.05) for pigs fed lactose or food-grade whey when compared to pigs fed feed-grade whey. There were no other differences in ADG or d 14 weights among the treatments. Average daily feed intake was improved (P<0.05) for pigs fed lactose, dextrose monohydrate, or food-grade whey when compared to those fed feed-grade whey. Feed efficiency was improved (P<0.05) for pigs fed food-grade whey rather than dextrose monohydrate. For the economic analysis, pigs fed the control diet had the lowest (P<0.01) cost per pound of gain, followed by pigs fed dextrose monohydrate, dextrose anhydrous, feed-grade whey, lactose, and food-grade whey. Margin-over-feed cost was improved (P<0.05) for pigs fed the control diet rather than the diets containing lactose, dextrose anhydrous, or either whey source. In Exp. 2, a total of 352 pigs (initially 17.1 lb) were used in a 14-d experiment to evaluate seven commercial whey sources. There were eight treatments consisting of a corn-soybean meal-based control diet and seven diets containing 10% whey, each of a different whey source. Pigs were blocked by weight and randomly allotted to treatment after being fed SEW and Transition diets for the first five days post-weaning. Overall, ADG and d 14 weight were improved (P<0.05) for pigs fed whey sources A and E when compared to the control and sources B and D. Pigs fed whey sources C, F, and G had intermediate ADG. Average daily feed intake was greater (P<0.05) for pigs fed whey source E rather than the control or whey sources B, C, D, and G. Feed efficiency was improved (P<0.05) for pigs fed whey source A rather than the control. Pigs fed the remaining whey sources had intermediate F/G. For the economic analysis, pigs fed the control diet had the lowest cost per pound of gain (P<0.01). Margin-over-feed cost was improved (P<0.05) for pigs fed the control diet rather than the diets containing whey sources B, D, and G. Pigs fed whey source A had intermediate MOF that was also greater (P<0.05) than that of pigs fed whey sources B and D. In conclusion, differences in the growth performance of pigs fed various whey (or lactose) and dextrose sources exist. The quality, cost, and relative feeding value of lactose sources should be considered when formulating diets for nursery pigs. In some cases, especially with the current high price of dried whey, feeding a Phase 2 diet containing no added source of lactose may be a more economical option despite the slight reduction in growth performance.
Keywords: Swine; Feed ingredients; Lactose; Dextrose; Whey